Implementation Occupational Health And Safety Communication In The Petrochemical Industry Of Kujang Fertilizer - Hanifah Handayani (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
The petrochemical industry is an industry engaged in the processing of chemicals using raw materials from the processing of petroleum and natural gas. The petrochemical industry has a high potential for hazards and work accidents.To prevent this, an Occupational Safety and Health (K3) program is needed. Accidents within the company can be minimized if the management is committed to K3 and one way is by communicating to employees to remain vigilant at work. The role of K3 communication is stated in Law No. 1 of 1970 and PP 50 of 2012.This research was conducted with literature studies and qualitative methods.The result: PT Pupuk Kujang has carried out K3 communication and K3 promotion not only during the national 3K month but has been routinely implemented K3 communication built at PT pupuk Kujang baik internally and externally, either directly or indirectly The implementation of K3 communication carried out by PT Pupuk Kujang is by applicable laws.